Employing antineutrino detectors to safeguard future nuclear reactors from diversions - Christopher Stewart (Nature Portfolio, 2019)
Nuclear reactors can be used for energy generation or for dangerous weapons and therefore their monitoring is crucial. Here the authors discuss detecting antineutrino from a nuclear reactor and use it for nuclear safeguards in a diversion scenario.